Competence Contribution in Work Environment and Job Satisfaction Performance over PTSP West Jakarta - Budhi Fahlevi; Tantri Yanuar Rahmat Syah; Husein Umar (Journal of Multidisciplinary Academic, 2019)
Public service performance is an interesting topic to be studied by experts and observers of public administration issues, because a public service in government activity must be answered the community needs to facilitate a permit and non-permit services over health, education, and economy problems. The government, through a employees in charges must provide certainty of security and convenience when the public need administrative services provide a sense of satisfaction. Here, the satisfaction toward excellent service from employees can be seen from information technology application, effective and efficient work procedures with quality of the work environment to response toward problems or conflicts during the service process. The change public service institutions are able to provide the best services in public. In this study aimed to analyze the effect of competence and work environment on job satisfaction and its impact on the performance of civil servants. This study assessed competence and work environment influence job satisfaction and employee’s performance. Here, we obtain all parameters data from employees especially civil servant staffs. Therefore, through the methods of pre-research surveys, we interviewed and give questionnaires. From the results, we found a correlation between the main factors that were very significant. Here, the respondents surveyed in this study were 200 civil servant staff working at the PTSP level in the village, district, and city of West Jakarta. The data were analyzed using Structural Equation Model (SEM) with data processing using Lisrel software. The results shows that competence and work environment influenced job satisfaction and had a significant impact on the performance of civil servants in PTSP West Jakarta.